Modeling and Modulation of NNPC Four-Level Inverter for Solar Photovoltaic Power Plant - Xiaoqiang Guo; Xuehui Wang; Ran He; Mehdi Narimani (International Journal of Photoenergy)
Photovoltaic (PV) power plant is an attractive way of utilizing the solar energy. For high-power PV power plant, the multilevel inverter is of potential interest. In contrast to the neutral-point clamped (NPC) or flying capacitor (FC) multilevel inverter, the nested neutral point clamped (NNPC) four-level inverter has better features for solar photovoltaic power plant. In practical applications, the common mode voltage reduction of the NNPC four-level is one of the important issues. In order to solve the problem, a new modulation strategy is proposed to minimize the common mode voltage. Compared with the conventional solution, our proposal can reduce the common mode voltage to 1/18 of the DC bus voltage. Moreover, it has the capability to balance the capacitor voltages. Finally, we carried out time-domain simulations to test the performance of the NNPC four-level inverter.